Correlation Between Total Lymphocyte Count and SOFA Score in Adult Sepsis Patients: A Cross-Sectional Study in An ICU Setting - Desmiko Haryo Wicaksono; Bastian Lubis; Luwih Bisono (Faculty of Medicine-Universitas Airlangga, 2026)
Introduction: Sepsis is a life-threatening organ dysfunction due to dysregulation of the host’s response to infection, which causes systemic changes, namely a decrease in the Total Lymphocyte Count value, which is related to mortality. Sepsis remains a major global health challenge due to its complex pathophysiology, heterogeneous clinical presentation, and high mortality despite advances in critical care management. Early identification of immune dysregulation is crucial for risk stratification and timely intervention. Simple, accessible, and cost-effective biomarkers derived from routine laboratory examinations are therefore needed to support early assessment of disease severity in patients with sepsis.Objective: This research is an observational analytical study with a cross-sectional approach in adult patients diagnosed with sepsis in integrated inpatient wards and intensive care wards at Haji Adam Malik Hospital Medan. Methods: The subject sampling technique used was non-probability sampling with a consecutive sampling method where 115 subjects were required. Bivariate analysis used the Spearman correlation test on the Total Lymphocyte Count value and SOFA score with a 95% confidence interval, with a p-value <0.05 considered significantly significant. Results and Discussion: The results of the research on the first day found that the average lymphocyte count was 0.92 + 0.29 (0.78) and the average SOFA score was 9.96 + 2.88 (11), where an r-value of -0.783 was obtained, which indicates a high and significant negative relationship between lymphocyte count and SOFA score as a predictor of sepsis patients (p-value = 0.001, p <0.05). Conclusion: Lymphocyte count has a strong negative correlation with the SOFA score in adult patients diagnosed with sepsis in integrated inpatient wards and intensive care wards.